Isolation, screening and identification of haloarchaea with chitinolytic activity from hypersaline lakes of Iran - Yavari-Bafghi, Maryam; Babavalian, Hamid; Amoozegar, Mohammad Ali (Archives of Biological Sciences, 2019)
Paper description: The industrial application of enzymes which can withstand harsh conditions has greatly increased in recent years and extremozymes are good alternatives to mesophilic enzymes in industries. Chitinase is one of the most important hydrolytic enzymes with a variety of biotechnological applications. We describe chitinase from a haloarchaeal strain belong to the genus Natrinema isolated from a hypersaline lake in Iran. To our knowledge, our investigation is among the first studies on chitinolytic activity of halophilic archaea. This study revealed the strong potential of the genus Natrinema to produce chitinase at high salt concentrations without Mg2+ requirement. Abstract: Halophiles produce stable enzymes under extreme conditions. The scant information about chitinolytic haloarchaea led us to conduct the present study in order to isolate and screen native halophilic archaea with chitinolytic activity and to optimize the enzyme production conditions. Among 500 haloarchaeal strains isolated from water samples from different hypersaline lakes of Iran, five strains showed chitinolytic activity. Based on biochemical, morphological and molecular analyses, we established that all five potent strains belonged to the genus Natrinema. Besides, observing chitinase function in culture media, through an additional molecular test the presence of the chitinase gene in chitinase-producing strains was also confirmed by PCR amplification. Compared with other potent strains, Natrinema sp. strain BS5 showed significant chitinase production. The production of chitinase in strain BS5 accompanied growth, started at the logarithmic phase and increased to its maximum level at the beginning of the stationary phase. Maximum chitinase production was obtained at 37˚C, pH 7.5, 3 M NaCl and 1% colloidal chitin. The strain BS5 showed 38%, 30%, 24% and 28% decreases in enzyme production at 40˚C, pH 8, 3.5 M NaCl and 0.5% substrate, respectively. This strain was able to produce the enzyme in NaCl 4 M and in the absence of MgCl2 and MgSO4. This study revealed the strong potential of the genus Natrinema to produce chitinase at high salt concentrations without Mg2+ requirement. https://doi.org/10.2298/ABS180525049Y Received: May 25, 2018; Revised: September 27, 2018; Accepted: October 4, 2018; Published online: October 30, 2018 How to cite this article: Yavari-Bafghi M, Babavalian H, Amoozegar MA. Isolation, screening and identification of haloarchaea with chitinolytic activity from hypersaline lakes of Iran. Arch Biol Sci. 2019;71(1):71-81.